Paz, territorio, Estado local y empresariado. Experiencias con el mecanismo de Obras por Impuestos en Risaralda (2020)
With the aim of establishing how Risaralda entrepreneurs relate to the construction of territorial peace in the Department —especially in the municipalities of the areas most affected by the armed conflict in Colombia (ZOMAC)—, 25 interviews were conducted with entrepreneurs as well as trade union, territorial, and State actors of various kinds. This allowed us to assess that, although a large part of the business sector (and its trade unions) in this Department are interested in using the Public Works Tax Incentives Mechanism as a way to contribute in the ZOMAC in favor of the construction of territorial peace, its implementation process has been slow and complex in the new environment of “peace with legality”.